Hepatitis B Vaccination of Low Birth Weight Infants in Washington State - Ost, Katarina; Oster, Natalia V.; Jacobson, Elizabeth N.; deHart, M. Patricia; Englund, Janet A.; Hofstetter, Annika M. (American Journal of Perinatology, 2020)
Objective The U.S. Advisory Committee on Immunization Practices (ACIP) recommends that infants born weighing less than 2,000 g receive the hepatitis B (HepB) vaccine at hospital discharge or 30 days of age. This study aimed to assess timely HepB vaccination among low birth weight infants. We hypothesized that many of these vulnerable infants would fail to receive their HepB birth dose on time.Study Design This retrospective cohort study included Washington State infants born weighing less than 2,000 g at an academic medical center between 2008 and 2013. Data were abstracted from electronic health records and linked to vaccine data from the Washington State Immunization Information System. Multivariable logistic regression was used to examine the associations between sociodemographic, clinical, and visit characteristics and HepB vaccination by birth hospitalization discharge or 30 days of age.Results Among 976 study infants, 58.4% received their HepB vaccine by birth hospitalization discharge or 30 days of age. Infants had higher odds of timely HepB vaccination if they were Hispanic (adjusted odds ratio [AOR] = 1.80, 95% confidence interval [CI]: 1.10–2.95) or non-Hispanic black (AOR = 2.28, 95% CI: 1.36–3.80) versus non-Hispanic white or if they were hospitalized 14 days or longer versus less than 14 days (AOR = 2.43, 95% CI: 1.66–3.54). Infants had lower odds of timely HepB vaccination if they were born before 34 weeks versus on or after 34 weeks of gestational age (AOR = 0.41, 95% CI: 0.27–0.63) or if they had an estimated household income less than $50,845 versus 50,845 or greater (AOR = 0.64, 95% CI: 0.48–0.86).Conclusion Many infants born weighing less than 2,000 g did not receive their first HepB birth dose according to ACIP recommendations. Strategies are needed to improve timely HepB vaccination in this high-risk population.Key Points
Keywords: hepatitis B; vaccination; low birth weight; infant; hospital